Toilet coupling - Emmerling, John F; Stonecipher, Scott W; Ahola, Billy Jack; Swart, Peter William (2019)
A method for securing a toilet tank to a toilet bowl through an attachment assembly. The method includes the steps of engaging a valve to the tank through an opening in the tank, moving a mounting bracket over the valve through an opening in the mounting bracket to position the mounting bracket adjacent to the tank, the mounting bracket having at least three mounting locations with fasteners attached thereto, coupling a valve nut to the valve to secure the mounting bracket between the tank and the valve nut, and securing the mounting bracket to the bowl through the fasteners. The at least three fasteners are disposed external to the tank and couple the tank to the bowl without directly engaging the tank.